A genome-wide association study for melatonin secretion - Pi-Hua Liu (Scientific Reports, 2022)
Abstract Melatonin exerts a wide range of effects among various tissues and organs. However, there is currently no study to investigate the genetic determinants of melatonin secretion. Here, we conducted a genome-wide association study (GWAS) for melatonin secretion using morning urine 6-hydroxymelatonin sulfate-to-creatinine ratio (UMCR). We initially enrolled 5000 participants from Taiwan Biobank in this study. After excluding individuals that did not have their urine collected in the morning, those who had history of neurological or psychiatric disorder, and those who failed to pass quality control, association of single nucleotide polymorphisms with log-transformed UMCR adjusted for age, sex and principal components of ancestry were analyzed. A second model additionally adjusted for estimated glomerular filtration rate (eGFR). A total of 2373 participants underwent the genome-wide analysis. Five candidate loci associated with log UMCR (P value ranging from 6.83 × 10−7 to 3.44 × 10−6) encompassing ZFHX3, GALNT15, GALNT13, LDLRAD3 and intergenic between SEPP1 and FLJ32255 were identified. Similar results were yielded with further adjustment for eGFR. Interestingly, the identified genes are associated with circadian behavior, neuronal differentiation, motor disorders, anxiety, and neurodegenerative diseases. We conducted the first GWAS for melatonin secretion and identified five candidate genetic loci associated with melatonin level. Replication and functional studies are needed in the future.